CHARACTERISTIC FEATURES OF PERCEPTION VERBS IN MODERN ENGLISH AND UZBEK (Conferencea, 2022)
This article deals with the study of verbs, particularly, perception verbs in Modern English and Uzbek. Perceptive verbs are considered as pole semantic verbs in English, which have more than one unique meaning.